THE PERCEPTION OF FISHERMAN ABOUT MANUBO CULTURE OF RIVER TAPUNG IN PETAPAHAN VILLAGE TAPUNG SUBDISTRICT KAMPAR PROVINCE RIAU. - Pebrianti, Riza; Hendri, Ridar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Research was conducted in the Petapahan Village Tapung Subdistrict KamparProvince Riau on January to February 2015. The research was aimed to determine theperception of fisherman about Manubo culture of River Tapung in Petapahan Village TapungSubdistrict Kampar Province Riau by the survey methode. The responden was determined bysensus. The result concluded the Manubo culture is fishing togheter with root of tuba once of ayear, exactly on dry season for aims to make a good relationship, growth the togheterness, andincrease community economy who need. The perception of fisherman about the Manuboculture are included on 3 ; they are ; (1).Manubo culture don’t have major impact on the fishingresult, (2).Manubo culture don’t have the major impact the quality of fish; (3).And theexistence of the Manubo culture is decreasing. For the score, the perception of fisherman aboutthe Manubo culture is less well categoried (20-27), and well (28-35). So, the perception offisherman about Manubo cluture have no major impact on fisheries resources pollution becauselimitedness of area and tuba.Keywords : Manubo culture, Perception of fisherman, impact.